2003
DOI: 10.1002/bit.10754
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic limitations in the synthesis of polyesters by lipase‐catalyzed ring‐opening polymerization

Abstract: Lipase-catalyzed polymerization of caprolactone (CL) in toluene with methoxy-poly(ethylene glycol) (MPEG) and water as initiators was characterized in detail for mechanistic insight. (1)H NMR analysis of polycaprolactone chains (PCL), dicaprolactone, degree of esterification of MPEG, and fractions of PCL chains initiated by MPEG and water were used to follow the reactions. The data were analyzed with the kinetic scheme involving formation of the acylenzyme and its consequent reaction with MPEG, water, or PCL t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 34 publications
2
32
0
Order By: Relevance
“…In general, this is not a limitation of the reaction because CALB catalyzed polymerizations of lactones are well-known from the literature so that enough water seems to be available even with dried enzyme preparations. 15,31,32 In the synthesis of poly(β-alanine) from β-lactam (1) reported by Schwab et al, 18 the authors could also show that in contrast to pathway B of Scheme 1, β-alanine (3) is not a substrate for the lipase catalyzed synthesis of poly(β-alanine), a surprising result that was confirmed in a variety of different solvents to rule out a solvent dependency. 29 This result is in agreement with the findings of Hollmann et al 25 who observed an inactivation of CALB by acids exhibiting a pK a below 4.8.…”
Section: ' Results and Discussionmentioning
confidence: 89%
“…In general, this is not a limitation of the reaction because CALB catalyzed polymerizations of lactones are well-known from the literature so that enough water seems to be available even with dried enzyme preparations. 15,31,32 In the synthesis of poly(β-alanine) from β-lactam (1) reported by Schwab et al, 18 the authors could also show that in contrast to pathway B of Scheme 1, β-alanine (3) is not a substrate for the lipase catalyzed synthesis of poly(β-alanine), a surprising result that was confirmed in a variety of different solvents to rule out a solvent dependency. 29 This result is in agreement with the findings of Hollmann et al 25 who observed an inactivation of CALB by acids exhibiting a pK a below 4.8.…”
Section: ' Results and Discussionmentioning
confidence: 89%
“…However, mechanistic limitations exist in such reactions, and these include the limit for methoxy-poly(ethylene glycol) initiator esterification and slower monomer conversion in concentrated solutions, factors that have been investigated by researchers (Panova and Kaplan 2003). Ultrasonic irradiation has been shown to greatly improve C. antarctica lipase B-mediated ROP of e-CL to poly-6-hydroxyhexanoate in the ionic liquid 1-ethyl-3-methylimidazolium tetrafluoroborate.…”
Section: Lipase-catalyzed Biopolymer Synthesis and Degradationmentioning
confidence: 99%
“…The scaled‐up reaction in toluene (45 °C for 24 h) increased the PCL molecular weight ( M n ) to ∼41 500 g mol ‐1 with 78% isolated yield and 1.69 PDI. Panova and Kaplan examined the effect of different ϵ‐caprolactone concentrations (0.065–7.8 mol L ‐1 ) on the Novozym 435‐catalyzed ROP in toluene at 70 °C, and suggested that both the monomer conversion and the degree of polymerization increased with monomer concentration (up to certain concentrations) and then decreased with further increase in the monomer concentration. The decreased monomer conversion in concentrated monomer solutions is probably due to the poorer partitioning of PCL between toluene and the lipase, which could lead to enzyme inhibition by the reaction product and/or slow diffusion of monomer to the enzyme active site.…”
Section: Enzymatic Rop In Organic Solventsmentioning
confidence: 99%